Pengaruh Model Pembelajaran Kooperatif Talking Stick Terhadap Hasil Belajar Kimia Siswa Kelas XI Pada Materi Koloid - Widiawati Widiawati; Jeckson Siahaan; Saprizal Hadisaputra (FKIP University of Mataram, 2025)
This study aims to examine the effect of the cooperative learning model Talking Stick on students’ learning outcomes in the colloid topic among Grade XI students at MA NWDI Wakan. A quasi-experimental method with a pretest–posttest control group design was employed. The sample consisted of 40 students from classes XI MIPA 1 and XI MIPA 2. Data were analyzed using N-Gain analysis, normality testing, homogeneity testing (F-test), and hypothesis testing with an independent t-test. The hypothesis testing at a significance level of α = 0.05 yielded a t-value of 3.972, which exceeded the t-table value of 2.024, indicating a significant difference between the experimental and control groups. These findings demonstrate that the implementation of the Talking Stick cooperative learning model has a positive effect on students’ learning outcomes in the colloid topic.